Subclinical Mastitis Prevalence on Small Scale Dairy Farming in Bogor - Henny Endah Anggraeni; Shania Zachra Nurfuadi (Journal of Applied Veterinary Science And Technology, 2021)
Background: Subclinical mastitis prevalence data in Bogor Regency is still lacking in every farm.  It is important to calculate the prevalence and evaluation of the causative factors for subclinical mastitis in dairy cows to maintain the quality and quantity of milk production and determine the most appropriate control. Purpose: The purpose of this study was to describe Subclinical Mastitis Prevalence on Small Scale Dairy Farming in Bogor. Method: The data collection was carried out by determining 126 dairy cows as an individual sample using simple random sampling. Sample testing was performed using the California Mastitis Test (CMT). Results: The results showed that the prevalence of subclinical mastitis in the farm area was still very high at 82.5% with the results of 104 positive and 22 negative. Conclusion: The causes of subclinical mastitis are sanitation and poor hygiene in the implementation of milking.